РЕДКОЗЕМЕЛЬНЫЕ МИНЕРАЛЫ КАРБОНАТИТОВ АРШАНСКОГО МЕСТОРОЖДЕНИЯ (ЗАПАДНОЕ ЗАБАЙКАЛЬЕ) - Булнаев К.Б.; Карманов Н.С. (My University, 2006)
Linear-fracture carbonatites of Arshanskoye ore deposit have been described as the rare earth's ones twenty years ago (Bulnacv, 1985, 2000). Elevated contents of lanthanides was explained then by presence of bastnacsite and orthite. At the same time there was remarked development of small parisite grains after phenocrysts of bastnacsite (Ripp с a., 2000). At the present study, parisite and orthite developed after bastnaesite have been examined under the electron misroscope with use of the energy dispersion analyzer. Investigation has shown the meta-somatic origin of both minerals and their essentially cerium composition. Chemical-spectral analysis defines also presence of Sm, Eu, Gd, Dy and Yb on the л ■ (0.001-0.1) % levels.
Keywords: 553.493:546.65